Jalur Berkelanjutan dari Instalasi Pengolahan Air Limbah Bengkong Sadai di Batam - Adicita, Yosef; Suryawan, I Wayan Koko (Civil Infrastructure Engineering and Architectural Design, 2024)
The urban center of Batam faces recurrent water crises. The introduction of the Bengkong Sadai Wastewater Treatment Plant (WWTP) offers a potential solution, converting domestic wastewater into reusable water, thereby addressing scarcity concerns. This research provides a comprehensive SWOT analysis of the WWTP, aiming to understand its potential for ensuring sustainable water management in Batam. We identified that while the WWTP capitalizes on state-of-the-art infrastructure, making a notable contribution to water reclamation and organic fertilizer production, it also confronts challenges like community engagement and operational complexities. Based on the analysis, the study emphasizes the criticality of proactive maintenance, robust stakeholder collaboration, and the need for a forward-thinking approach. This work sheds light on Batam's endeavors and offers a blueprint for other urban locales grappling with similar challenges.